2006
DOI: 10.1063/1.2185621
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the polar {111} NaCl crystal face

Abstract: We present a surface x-ray diffraction determination of the ͕111͖ NaCl-liquid interface structure. Using ultrathin water or formamide liquid layers we ascertained that the crystal surface is smooth at an atomic level and is not reconstructed. Our results reveal surprisingly small differences in surface structure between the two cases, which nevertheless lead to dramatic differences in crystal morphology. We determined that the rocksalt ͕111͖ surface is Na + terminated for both environmental conditions. A quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 29 publications
(26 reference statements)
0
38
0
Order By: Relevance
“…Compared to this result the Na + terminated surface therefore shows a much better adhesion energy suggesting that the (111) surface of NaCl grown in the presence of formamide could be terminated by Na + ions. The same proposal was put forward by Radenović et al based on the analysis of the atomic charges for the formamide molecule 19 and by means of a SXRD study 21 . …”
Section: The 2d Epitaxy 101 Formamide / 111 Nacl Viewed Through Tmentioning
confidence: 94%
“…Compared to this result the Na + terminated surface therefore shows a much better adhesion energy suggesting that the (111) surface of NaCl grown in the presence of formamide could be terminated by Na + ions. The same proposal was put forward by Radenović et al based on the analysis of the atomic charges for the formamide molecule 19 and by means of a SXRD study 21 . …”
Section: The 2d Epitaxy 101 Formamide / 111 Nacl Viewed Through Tmentioning
confidence: 94%
“…A regular, uniform layer of positive ions on the surface of a crystal may give it a polar character with the result that its energy tends to infinity with increasing surface area, as found already by Stranski for the case of the {1 1 1} form of the NaCl lattice [20]. Recently, however, it has been demonstrated by Radenovic´et al [22][23][24] that such a crystal face may be stabilized by factors like incomplete occupancy of the outmost layers and then behave like an F face on the growing crystal. Furthermore, crystals of many metal oxides and other electrolytes with basic anions are, in fact, protonated in aqueous solution at low pH [25,26].…”
Section: Adsorption Equilibrium Of Protonsmentioning
confidence: 87%
“…The AFM data were interpreted by considering the bulk truncated surface structures. According to SXRD experiments by Radenovic´et al [13], no reconstruction was observed even for the polar NaCl(1 1 1) surface [13].…”
Section: Methodsmentioning
confidence: 95%